Test for effect of welding layers on girth weld toughness of X80 pipeline steel - Ting WANG; Jian CHEN; Shengyi SHA; Lianshuang DAI; Peng YANG; Xiaohui ZHAO (You-qi chuyun, 2022)
The girth welds of natural gas pipelines applied by self-shielded flux cored semi-automatic welding process in multiple layers and passes are prone to failure, and the main reasons include the number of welding layers is less than that required by the process, the single-pass welding layer is too thick, and welding principles are not met. These problems can cause excessive input of welding heat, which affects the weld structure and leads to the decline of girth weld toughness. Hence, the study was performed based on the X80 pipeline steel by the semi-automatic welding process using the self-shielded flux cored wire. Specifically, the toughness test results, metallographic structure and fracture of the girth weld zone and heat affected zone with different welding layers were analyzed comparatively. The results show that, with the increase of welding layers, the impact toughness of weld is greatly improved and the dispersion is reduced, the toughness ratio of fracture morphology increases, the grains are continuously refined and staggered with each other, which can effectively prevent the crack propagation. Generally, the research results could play a guiding role in formulating the welding procedure specification of natural gas pipeline and strengthening the quality management of construction on site.